2017
DOI: 10.1093/aje/kww207
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoid and Lignan Intake and Mortality in Prospective Cohort Studies: Systematic Review and Dose-Response Meta-Analysis

Abstract: Recent evidence has suggested that flavonoid and lignan intake may be associated with decreased risk of chronic and degenerative diseases. The aim of this meta-analysis was to assess the association between dietary flavonoid and lignan intake and all-cause and cardiovascular disease (CVD) mortality in prospective cohort studies. A systematic search was conducted in electronic databases to identify studies published from January 1996 to December 2015 that satisfied inclusion/exclusion criteria. Risk ratios and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 237 publications
(170 citation statements)
references
References 57 publications
7
163
0
Order By: Relevance
“…The length of the open-ended category was assumed to be the same as that of the neighboring category when the highest category was open-ended. 15,16 Heterogeneity between studies was evaluated using the Q statistic (ie, a measure of weighted squared deviations) and the I 2 (ie, the proportion of total variation explained by variation between studies). We used Q and degree of freedom to check whether the heterogeneity was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the open-ended category was assumed to be the same as that of the neighboring category when the highest category was open-ended. 15,16 Heterogeneity between studies was evaluated using the Q statistic (ie, a measure of weighted squared deviations) and the I 2 (ie, the proportion of total variation explained by variation between studies). We used Q and degree of freedom to check whether the heterogeneity was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown associations between a diet rich in polyphenols and the prevention of human diseases [12,17,18,19,20,21]. Polyphenols are natural anti-oxidants present in the human diet.…”
Section: Polyphenolsmentioning
confidence: 99%
“…The intake of these bioactive compounds are thought to contribute to the health benefits associated with the consumption of such foods [3]. Polyphenols are some of the most abundant phytochemicals in plant foods and increasing evidence from cohort studies indicate that the intake of some of these compounds such as diverse flavonoids and/or, importantly, some of their derived microbial metabolites (e.g., enterolactone) may help to reduce the development of CVDs and CVDs mortality risk [4,5,6,7]. This evidence is supported by animal and clinical studies reporting beneficial effects of the consumption of some polyphenol-rich foods or pure compounds on CVDs risk factors such as blood cholesterol, blood pressure, endothelial function and arterial stiffness [8].…”
Section: Introductionmentioning
confidence: 99%